2012
DOI: 10.1016/j.jvs.2011.12.069
|View full text |Cite
|
Sign up to set email alerts
|

Twenty-year review of abdominal aortic aneurysm screening in men in the county of Gloucestershire, United Kingdom

Abstract: Screening reduced the number of ruptured AAAs in Gloucestershire during the 20 years of the program. There has been a significant reduction of men with an abnormal aorta, as the mean aortic diameter of the 65-year-old male has reduced over 20 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
92
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 31 publications
2
92
1
2
Order By: Relevance
“…14 This study also reported data on AAA diameter, unlike the MASS study. We estimated the number of men whose care or death was not influenced by the diagnosis-that is, their AAA remained asymptomatic over the course of the study.…”
Section: Proportion Of Men Who Do Not Benefit From Diagnosismentioning
confidence: 90%
“…14 This study also reported data on AAA diameter, unlike the MASS study. We estimated the number of men whose care or death was not influenced by the diagnosis-that is, their AAA remained asymptomatic over the course of the study.…”
Section: Proportion Of Men Who Do Not Benefit From Diagnosismentioning
confidence: 90%
“…Since then, results from completed and on---going screening studies and programmes have been published, among other things revealing that the prevalence is considerably lower, the attendance rate is higher, the rate of opportunistic detection is greater, the costs associated with surgery have changed, e.g. due to shorter ICU---stay and increased use of EVAR, operative mortality rate has decreased and general survival (not related to AAA) in the population has increased (Svensjo et al 2011, Darwood et al 2012. Although previous studies have indicated that screening for AAA appears cost---effective and that the results are robust to changes in input parameters, updated analyses in a different context are warranted due to changed circumstances and the availability of data from screening programmes in healthcare practice.…”
Section: Areas Studied In This Thesismentioning
confidence: 99%
“…5,6 AAA screening has been ongoing in Gloucestershire in the UK for nearly 25 years. 7 The results of interventions for men with screen-detected AAA have been reported. In brief, men are invited to attend their general practitioner's (GP) surgery for ultrasound screening in the year that they are 65 years of age (all surgeries in Gloucestershire are visited at least annually).…”
Section: Introductionmentioning
confidence: 99%